Analysis of Rotation Speed Effect on NaCl Content of Salt in The Salt Washing Process: Analysis of Rotation Speed Effect on NaCl Content of Salt in The Salt Washing Process - Edi Sutoyo; Tika Hafzara Siregar; Setya Permana Sutisna; Musta'anul Husaini Hasibuan; Meilani Aulia Putri; Atiqotun Fitriyah (Universitas Ibn Khaldun Bogor, 2023)
Salt is a solid and crystalline substance produced from sea water. The salt that we know has a collection of compounds whose main part is Sodium Chloride (NaCl) as well as several impurities such as Calcium Sulfate (CaSO4), Magnesium Sulfate (MgSO4), Magnesium Chloride (MgCl2) and others. The washing process needs to be carried out to remove impurities so that NaCl levels on salt increase. The washing process with stirring in several rotation variations was used to increase the NaCl content on salt. This research aimed to determine the effect of the rotation speed of the stirrer blade in the washing process in increasing the NaCl content on salt. This research used variations in rotation speed of 40 rpm, 80 rpm, and 120 rpm and compared the increasing trend with washing times of 15 minutes and 20 minutes. The experiment showed the best rotation speed in the washing process to obtain the greatest salt content is a rotation speed of 80 rpm. Experiment with variations in rotation speed with washing times of 15 minutes and 20 minutes showed that increasing the rotation speed did not have a significant effect on increasing NaCl content of salt in the washing process.